Understanding How They Work: The Agents’ Strategies in Producing Indonesian-English Literary Translation - M. Yuseano Kardiansyah; Aprinus Salam; Nur Saktiningrum (Journal of Language and Literature, 2023)
This article contains a study on Yogyakarta literary agents’ strategies in producing a translated work from Indonesian into English (Indonesian-English literary work) entitled “Pilgrimage in the Land of Java”. Due to the development of literary studies based on the practice of its agents, this study aims to understand more the pattern and vision of agents in producing translated literary work in a particular context. In this case, the agents are a poet Iman Budhi Santosa, an indie publisher Interlude, and a translator Chrysogonus Siddha Malilang. This study adopts the Bourdieusian concept of strategy in cultural production as the framework of thought. Meanwhile, interview and document selection are two primary techniques to collect data for this qualitative research. This study reveals the strategies implemented by the three primary agents during the production of “Pilgrimage in the Land of Java”. Although running on the same track, it turns out that each of them had specific strategies based on the role that they possessed during the production. This study also discloses the significance of social capital in translation practice.